PENERAPAN ALGORITMA APRIORI DALAM MENENTUKAN POLA PEMBELIAN KONSUMEN DI KAFE HIDDEN TOAST AND FLOAT - Ridwan Rismanto; Lucki Darmawan; Arief Prasetyo (Jurnal Teknologi Informasi dan Terapan, 2019)
Progress in Information Technology encourages culinary businesses to innovate, one of them is a computerized system, online-based sales and several interesting features that can increase consumer interest and increase sales to be the most frequently used innovation today. The cafe "Hidden Toast and Float" is a cafe in the City of Kediri. To increase sales from the cafe, a system is needed to facilitate the owner in recording sales and increasing the number of sales by providing automatic menu recommendations to customers. Based on the problem, in this thesis a website-based sales system and sales system will be created that is accompanied by the application of a priori algorithm to determine the purchasing patterns of customers and automatic menu recommendations from the system for customers. The test results of this thesis are two website-based systems with admin systems used to process existing data on the database and customer websites that are used for online purchases, as well as the application of a priori algorithms with the results of testing sample data and real data that produce menu combination recommendations. most often purchased based on all transaction data, namely Dark Choco Jam and Cappucino with a support value of 15% and a confidence value of 45%.